2022
DOI: 10.3390/ijerph19042264
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Biomarkers of Metal Exposure and Dry Eye Metrics in Shipyard Welders: A Cross-Sectional Study

Abstract: Shipyard welders are often exposed to welding metal fumes. Ocular surfaces are continually exposed to environmental hazards. However, limited information on the associations between metal exposure and dry eye metrics in occupational settings is available. This study employed a cross-sectional design that involved the participation of 59 welders and 25 administrative staff in a shipyard in northern Taiwan from September 2020 to October 2020. The participants’ individual information, laboratory data, exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…All included articles and the identified SDoH in each study are summarized in Table 1. Dry eye/ocular surface [18 ▪▪ ,19 ▪ –38 ▪ ] (21 articles) was the most prevalent cornea condition, followed by pterygium [39 ▪▪ ,40 ▪ –42 ▪ ] (4 articles), keratoplasty [43 ▪▪ ,44–46] (four articles), keratoconus [47 ▪ ,48,49] (three articles), cornea donation [50,51 ▪▪ ,52 ▪▪ ] (three articles), cornea thickness [53 ▪ ,54 ▪ ] (two articles), trachoma [55 ▪▪ ,56] (two articles), corneal ulcers [57 ▪ ,58 ▪ ] (two articles), corneal arcus [59 ▪ ] (one article), and corneal opacity[60 ▪ ] (one article). Cornea donation for transplantation was also explored.…”
Section: Search Results and Studies Included In The Reviewmentioning
confidence: 99%
“…Heavy metals have been also shown to be associated with dry eye disease. A large population study in Korea demonstrated an association between the detection of serum mercury and development of dry eye disease among females, while a cross-sectional study of welders in Taiwan reported associations between high levels of urinary cadmium and toenail lead concentrations, and dry eye disease [ 81 , 82 ].…”
Section: Proposed Mechanisms Of Tissue and Cell Damagementioning
confidence: 99%
“…They attribute the vulnerability of metal workers to dry eye disease to their exposure to dust and chemicals. In a cross-sectional study of welders in Turkey, exposure to cadmium and lead were correlated with dry eye disease [ 173 ]. Chen et al also found lead exposure and presence of lead in tears to be associated with dry eye disease [ 174 ].…”
Section: Workplace Ocular Injuriesmentioning
confidence: 99%